2013
DOI: 10.3126/ije.v2i1.9220
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Toxicity Of High Molecular Weight Polynuclear Aromatic Hydrocarbon- Pyrene On Freshwater Cyanobacterium Anabaena Fertlissima Rao

Abstract: The aim of this work was to determine the consequences of Polynuclear aromatic hydrocarbon – Pyrene in response to growth, pigments and metabolic study on Anabaena fertilissima Rao. Test organisms were treated at different doses and encountered LC50 (Lethal concentration at which 50% growth reduction occur) concentration separately at 1.5 mg/l, 3.0 mg/l and 6.0 mg/l respectively for Anabaena fertilissima Rao. The influence of Pyrene on growth, pigments, release of metabolites such as carbohydrates, protein, am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…The influence of pyrene, a polyaromatic hydrocarbon pollutant of growing concern, was investigated in a similar way in Synechocystis sp., Anabaena fertilissima and Nostoc muscorum. In this case, a comparable response to that of anthracene was obtained (Patel et al 2013; Kumar et al 2014). Very recently, Zhang et al (2018) studied the effects of pyrene and naphthalene on the growth rate, phycobiliprotein concentration, microcystin content and antioxidant enzyme activity of Microcystis aeruginosa .…”
Section: The Response Of Cyanobacteria To the Presence Of Aromatic Cosupporting
confidence: 61%
“…The influence of pyrene, a polyaromatic hydrocarbon pollutant of growing concern, was investigated in a similar way in Synechocystis sp., Anabaena fertilissima and Nostoc muscorum. In this case, a comparable response to that of anthracene was obtained (Patel et al 2013; Kumar et al 2014). Very recently, Zhang et al (2018) studied the effects of pyrene and naphthalene on the growth rate, phycobiliprotein concentration, microcystin content and antioxidant enzyme activity of Microcystis aeruginosa .…”
Section: The Response Of Cyanobacteria To the Presence Of Aromatic Cosupporting
confidence: 61%
“…The toxicity of each chemical differs from one organism to another (Patel et al 2013). Delisle et al (1977) and Greenwood et al (1984), studied sulphates and found that high values of this parameter can be observed in polluted streams, at the level of industrial waste areas (mining industry, pulp and paper mills, tanneries, textile mills).…”
Section: Toxicity Testmentioning
confidence: 99%
“…Besides, high organic carbon and total nitrogen, PAHs, heavy metal concentrations, low soil fertility index, pH and low moisture contents probably dwindle the growth of fungal strains in the contaminated soil. Patel et al (2013) determined the consequences of Polynuclear aromatic hydrocarbonPyrene in response to growth, pigments and metabolic study on Anabaena fertilissima Rao. This study therefore suggests high molecular weight pyrene that decreases in metabolite content and enzyme activity can be used as a signal of PAHs toxicity in cyanobacteria.…”
Section: 'This Journal Provides Immediate Open Access To Its Contentsmentioning
confidence: 99%